Management of mixed weeds in young oil-palm plantation with selected broad-spectrum herbicides - Mohamad, Rosli; Wibawa, Wahyu; Mohayidin, Mohd Ghazali; Puteh, Adam; Juraimi, Abdul Shukor; Awang, Yahya; Mohd Lassim, Mohammad (Universiti Putra Malaysia Press, 2010)

(untitled)
A field study to evaluate the efficacy of three broad spectrum herbicides on mixed weed in a young (2 yearold) oil palm plantation was conducted. Experimental plots, with the size of 4.8 x 20.5 m2 each, were laid in a randomized complete block design with 4 replications. Weed vegetation analysis was conducted before herbicide treatments were applied. Herbicide treatments used were paraquat and glufosinate-ammonium (200, 400, 600, 800 g a.i. ha-1), and glyphosate (400, 800, 1200, 1600 g a.i. ha-1), with untreated control. The experimental locality indicated a composite of mixed weeds of broadleaf and grasses. The growth of broadleaf was more dominant with 25 species (relative dominance of 82.1%) than the grasses with only 7 species (relative dominance of 17%). The three most dominant species were the broadleaves of Croton hirtus and Asystasia gigantica, and a grass, Paspalum commersonii. The percentage of the mixed weed composite killed was found to be significantly affected by the treatments of paraquat, glufosinate–ammonium and glyphosate, relative to the untreated control, with more than 50 percent weed killed taken at 2 and 4 WAT. Meanwhile, glyphosate and glufosinate-ammonium produced greater efficacy (more than 90 percent killed) as compared to paraquat which produced lower total weed killed (50 to 83%). There were positive correlations between the percentages of weed killed and weed growth reduction. Increased percentage of weed killed was followed by the increase in the percentage of weed growth reduction, with the indication that weeds were recovering and began to produce new shoots at 16 WAT. Treatments producing fewer efficacies caused weeds to regrow and recover faster or in a shorter time. Increased rates of paraquat treatments, i.e. from 200 to 600 and 800 g a.i. ha-1, were found to increase the duration of effective weed control. The duration of effective weed control produced by glufosinate-ammonium at 200 to 800 g a.i. ha-1 and glyphosate at 400 to 1600 g a.i. ha-1 ranged from 14.5 to 15 weeks, which were significantly longer than the paraquat treatments. The increased rates of glufosinate-ammonium and glyphosate did not necessarily increase the duration of effective control.